Living large the skinny guy's guide to no-nonsense muscle building - Del Monte, Vince (BenBella Books, 2016)
"Skinny guys! If you've ever wanted to easily pack 30 pounds of rock-solid, shredded muscle - without dangerous bodybuilding drugs, expensive supplements, and long hours in the gym, then you must read this book. Let's face it: You're tired. Tired of filling your body with bogus supplements that only give you the most expensive pee in town. Tired of busting your ass in the gym six days a week, only to find you're the same size you were last month and the other guys are twice as big. Tired of all the conflicting and mind-numbingly complex advice floating around in cyberspace. Before professional fitness model Vince Del Monte became The Skinny Guy Savior, he was known as Skinny Vinny-scrawny and weak. He experienced firsthand the challenges of bulking up as a "hardgainer," someone who has a difficult time putting on muscle. But with his success in developing an enviably ripped physique-and helping many others do the same with his No-Nonsense Muscle Building program-Del Monte has proved even "hardgainers" can get big. You too can have the body of your dreams and put on muscle when you stop being misinformed and learn the truth of gaining weight and building lean muscle mass-the right way! In Living Large, Del Monte shares his foolproof and no-nonsense plan for insane muscle gain. His revolutionary program primes your body and mind to pack on your first 30 pounds of muscle in only 30 weeks, with minimal gym time and virtually no fat. He even includes customized, easy-to-follow meal plans to optimally fuel your specific body type, whether you're ultra-skinny, "skinny fat," or starting off a little chubby. In Living Large, you'll find: The number-one secret to achieving constant and never-ending progress 5 "Always True" training and nutrition principles 3 scientifically supported mechanisms of rapid muscle growth A killer 18-week step-by-step workout program with three phases 4 supplements that actually work Full-color photo-illustrated exercise guide with Vince's tips for maximum effectiveness Don't waste HUNDREDS of hours and THOUSANDS of dollars with no results. Stop limiting yourself and start living large"--